2012
DOI: 10.1128/jcm.02078-12
|View full text |Cite
|
Sign up to set email alerts
|

Female Epidemiology of Transcription-Mediated Amplification-Based Trichomonas vaginalis Detection in a Metropolitan Setting with a High Prevalence of Sexually Transmitted Infection

Abstract: bRecent literature has reported increased accuracy of Trichomonas vaginalis transcription-mediated amplification (TMA)-based analyte-specific reagent (ASR) testing in female populations. A retrospective investigation assessed 7,277 female first-void urine, cervical, or vaginal specimens submitted from a high-prevalence sexually transmitted infection (STI) community to characterize prevalence of disease etiologies. The most common STI phenotype reflected detection of solely T. vaginalis (54.2% of all health car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
17
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 26 publications
(39 reference statements)
4
17
1
Order By: Relevance
“…Therefore, comparison of performance characteristics by specimen source could not be accomplished in this retrospective assessment. Of further interest, previous studies in our female patient population demonstrated increased T. vaginalis detection from first-void urine specimens (25,35). We also show increased T. vaginalis detection from first-void urine compared to cervical specimens (P ϭ 0.04; Fig.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Therefore, comparison of performance characteristics by specimen source could not be accomplished in this retrospective assessment. Of further interest, previous studies in our female patient population demonstrated increased T. vaginalis detection from first-void urine specimens (25,35). We also show increased T. vaginalis detection from first-void urine compared to cervical specimens (P ϭ 0.04; Fig.…”
Section: Discussionsupporting
confidence: 61%
“…Our data show elevated rates of M. genitalium detection in females, with significantly greater rates than those for Trichomonas vaginalis-a pathogen previously demonstrated to be present in abundance in the high-prevalence Milwaukee STI community (24,25). Of 282 detections of M. genitalium, 237 were subjected to confirmation by repeat testing or alternative-target TMA; 98.7% of such tests yielded a positive result.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to female populations that exhibit increased T. vaginalis detection versus C. trachomatis (19,20), T. vaginalis detection in our male population was not significantly less than C. trachomatis. This finding is relatively novel due to a perceived lack of laboratory diagnostic options for T. vaginalis in males.…”
Section: Discussioncontrasting
confidence: 39%
“…This finding is relatively novel due to a perceived lack of laboratory diagnostic options for T. vaginalis in males. The male STI phenotype for T. vaginalis, C. trachomatis, and N. gonorrhoeae, although exhibiting no significant difference between first-void urine and urethral specimen sources (Table 1), differed markedly from traditional female STI phenotype data (20)(21)(22). In general, a 17 to 24% increase in sole detection of T. vaginalis over C. trachomatis was observed in female populations with STI versus the ϳ5% difference noted in this male population.…”
Section: Discussionmentioning
confidence: 72%
“…Studies in US showed that the mean age of women and men infected with T. vaginalis were significantly higher than those infected with other STIs and the average age of T. vaginalis infected men was almost a decade older than in infected women (Munson et al 2012(Munson et al , 2013. In men, it may be partly due to age specific sexual partnerships with older infected women and changes in reproductive hormone levels have been suggested to contribute to higher T. vaginalis prevalence (Poynten et al 2013).…”
Section: Discussionmentioning
confidence: 96%